2015
DOI: 10.1007/s00265-015-2046-2
|View full text |Cite
|
Sign up to set email alerts
|

Ant larvae regulate worker foraging behavior and ovarian activity in a dose-dependent manner

Abstract: Division of labor in insect societies relies on simple behavioral rules, whereby individual colony members respond to dynamic signals indicating the need for certain tasks to be performed. This in turn gives rise to colony-level phenotypes. However, empirical studies quantifying colony-level signal-response dynamics are lacking. Here, we make use of the unusual biology and experimental amenability of the queenless clonal raider ant Cerapachys biroi, to jointly quantify the behavioral and physiological response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…However, the effect of larvae on the allocation of tasks across individual workers remains elusive in many social insects due to the challenges associated with measuring individual behavior in groups and precisely controlling brood demand. By taking advantage of automated tracking and the unique biology of the clonal raider ant, our study overcomes these challenges and advances our understanding of larval factors that affect task allocation: we suggest that brood demand and its effects on task allocation depend not only on the presence and number of larvae (37, 59), but also on larval genotype. These results also provide insights into previous cross-fostering experiments that revealed that interactions between worker and brood genotypes have non-linear effects on brood development (into intercastes vs. regular workers) (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of larvae on the allocation of tasks across individual workers remains elusive in many social insects due to the challenges associated with measuring individual behavior in groups and precisely controlling brood demand. By taking advantage of automated tracking and the unique biology of the clonal raider ant, our study overcomes these challenges and advances our understanding of larval factors that affect task allocation: we suggest that brood demand and its effects on task allocation depend not only on the presence and number of larvae (37, 59), but also on larval genotype. These results also provide insights into previous cross-fostering experiments that revealed that interactions between worker and brood genotypes have non-linear effects on brood development (into intercastes vs. regular workers) (38).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, ants can also vary in other traits, for example in the efficiency with which they perform tasks (3335) or in the average time spent performing a given task (36). Task demand can be similarly variable: for example, foraging activity levels of workers increase with the number of larvae that they have to tend to (37), and larvae of different genotypes develop into adults with different morphologies when cared for by the same workers (38). Thus, the level of demand emanating from the larvae could depend on their number and genotype.…”
Section: Introductionmentioning
confidence: 99%
“…This allows precise experimental manipulation of the cycle by adding or removing larvae of a particular developmental stage at standardized time points during the cycle (Figure 1). At the same time, O. biroi affords maximal control over the genetic composition and age structure of experimental colonies, arguably the two most important factors that affect division of labor in social insects (21,(25)(26)(27). This study takes advantage of the unique biology of O. biroi to investigate the molecular underpinnings of reproductive and brood care behavior, compare general patterns of gene expression between transitions, and identify candidate genes potentially involved in the evolutionary transition from subsocial to eusocial living.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the phasic cycles of Eciton and Neyvamyrmex have been extensively studied in the field throughout the 20th century (Hagan, 1954a, 1954b, 1954c, Schneirla, 1934, 1945, 1944a, 1944b; Topoff et al, 1980; Topoff, 1984), the “clonal raider ant” Cerapachys biroi is the only species in which the mechanistic aspects of phasic colony cycles have been thoroughly studied in highly controlled laboratory experiments (Ravary and Jaisson, 2002; Ravary et al, 2006; Teseo et al, 2013; Ulrich et al, 2015). In this parthenogenetic queenless species, the presence of larvae inhibits the ovarian activation in workers and stimulates foraging behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular, individual and colony-level mechanisms underlying the alternation of phases are now beginning to be understood (Ravary and Jaisson, 2002; Ravary et al, 2006; Teseo et al, 2013; Oxley et al, 2014; Ulrich et al, 2015), the adaptive significance of the phasic lifestyle is still to some extent unknown. At present, a single study (Kronauer, 2009) has formulated explicit hypotheses about the adaptive value of the phasic lifestyle, suggesting that it likely provides several main benefits.…”
Section: Introductionmentioning
confidence: 99%